The Interweaving of Everyday and Structural Perspectives: Exploring Suburban Struggles of Everyday Life - Marius Mlejnek; Petra Lütke (Urban Planning, 2023)
Everyday life is a central element for understanding the (sub)urban. Broader forces shape the (sub)urban and manifest in both its geographical structures and everyday life. These forces also shape globalized and complex urban contexts. Recent debates have addressed the question of which research designs best decipher this interplay. We argue that the struggles of everyday life could be a fruitful starting point for (sub)urban studies. Our research on socio-spatial changes in suburbia shows that these struggles emerge in a multidimensional field of tension. The concept of struggles of everyday life simultaneously acknowledges the relevance of the everyday and the impact of structural forces. We demonstrate this with our research design, the essential elements of which are literature work, narrative-episodic interviews, expert interviews, vignettes, and a hermeneutic, iterative research process. Conceptually, our research is based on the epistemological framework of planetary urbanization and Henri Lefebvre’s perspective on everyday life. We outline which conceptual and methodical approaches are useful for deciphering the interweaving of everyday life and structural forces, through the example of a suburb of the City of Cologne, Germany. Thereby, we provide remarks on recent questions of comparative urbanism in conceptual and methodological terms.